STRATEGI HUBUNGAN INDUSTRIAL DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN PT.ESAPUTLII PRAKARSA UTAMA KABUPATEN BARRU - Muliyani , Muliyani; Zelfia, Zelfia; Idris , Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This study aims to determine the development of an industrial relations strategy program as an effort to increase employee motivation and to determine the condition of the organizational communication climate that exists between management and employees at PT. Main Initiative Esaputlii. This study used descriptive qualitative method. The results showed that PT. Esaputlii Prakarsa Utama has succeeded in carrying out the industrial relations program because it has received a fairly good response from employees as well as employees who are quite satisfactory through programs, special events programs, award programs, and internal communication media programs. Likewise with the organizational communication climate applied by PT. Esaputlii Prakarsa Utama with behavior that shows to the core, warm but still responsible.